Preaching With Freshness - Mawhinney, Bruce (Grand Rapids, MI Kregel Publications, 1997)
The reality of ministry is that pastors often struggle-they struggle with the week-to-week demands of ministry that sap the physical and spiritual energy needed for sermon preparation and presentation. The result is that many pastors feen "buned out" in
Keywords: Preaching -- United States. Christian literature, American. Clergy -- United States -- Appointment, call, and election